Muhammad Rashid Reda and his Approach to his Interpretation of Al-Manar - Musleh , Muhammad; Khalaf , Abdullah (Islamic Sciences Journal, 2023)
One of the well-known figures in our Islamic world is Sheikh Muhammad Rasheed Ridha, who was educated on the goodness of morals, as he is persistent in reading the Noble Qur’an and dhikr, and he was courageous in telling the truth about rulers and scholars. He has combiled an interpretation for the Holy Quran. He has followed one unified , style while interpreting the whole Quran. Many of modern scientists have written about this interpretation, how he has interpreted the Quran by the Quran, the Quran by the sunnah, and the Quran by the sayings of linguists which supports his own style in adopting the Holly Quran.